Sikap Bahasa Mahasiswa Multikultural di Fakultas Brahma Widya Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar Terhadap Mata Kuliah Bahasa Bali - Ni Luh PT. Putriyani Dewi (Jayapangus Press, 2023)
The existence of Balinese language courses at a university received various responses from students at the university. Moreover, a university has students who come from different cultures, such as multicultural students at the Brahma Widya Faculty of UHN IGB Sugriwa Denpasar. The responses that come out cause different language attitudes between students from one another. Based on this background, the problems discussed in this study are how the language attitudes of multicultural students at the Brahma Widya Faculty of UHN IGB Sugriwa Denpasar towards Balinese language courses. This study aims to describe the language attitudes of multicultural students at the Brahma Widya Faculty of UHN IGB Sugriwa Denpasar towards Balinese language courses. The population of this research is the students of UHN IGB Sugriwa Denpasar, precisely at the Brahma Widya Faculty, Department of Hindu Theology in the 2021/2022 academic year with a total of 29 students selected through the total sampling technique. The method of data collection was carried out using a language attitude questionnaire/questionnaire using three characteristics of language attitudes according to Gavin and Mathiot. The data analysis technique used is descriptive qualitative which is then followed by qualitative verification. The results showed that the language attitude of the students of the Brahma Widya Faculty of UHN IGB Sugriwa Denpasar showed a tendency for positive language attitudes in Balinese language courses. This can be seen from the three characteristics of students' positive language attitudes, namely language loyalty, language pride, and awareness of norms in the main language of Balinese. Even though they come from areas with different cultures, these multicultural students have great motivation in learning languages, especially Balinese language is included in the courses they get during their education at UHN IGB Sugriwa Denpasar.